1970
DOI: 10.1083/jcb.46.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Ultrastructural Changes in the Frog Ovarian Follicle in Response to Pituitary Stimulation

Abstract: Frog ovarian fragments were prevented from ovulating in vitro by the addition of actinomycin D up to 3 hr following pituitary stimulation ; but addition of Actinomycin D 6 hr after stimulation was far less effective . Puromycin, on the other hand, effectively inhibited ovulation when added as late as 6 hr after pituitary stimulation . Although actinomycin D reduced uptake of uridine-3H, and puromycin reduced uptake of leucine 8H and lysine-14C by pituitary-stimulated ovarian tissue minus oocytes (OTMO) in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…She has demonstrated a sparse supply of smooth-muscle cells in the theca of ovarian follicles, and the presence of smooth-muscle fibres in the mesovarium. Anderson and Yatvin (1970) were unable to detect smooth-muscle cells in the follicle wall of the frog ovary. In the Pacific treefrog, Larsen et al (1977) have reported a non-muscular contractile system, constructed by inner ovarian epithelium cells, and they have shown that smooth-muscle cells are present in the theca of interfollicular regions, but never in the follicle itself.…”
Section: Biological Resultsmentioning
confidence: 93%
“…She has demonstrated a sparse supply of smooth-muscle cells in the theca of ovarian follicles, and the presence of smooth-muscle fibres in the mesovarium. Anderson and Yatvin (1970) were unable to detect smooth-muscle cells in the follicle wall of the frog ovary. In the Pacific treefrog, Larsen et al (1977) have reported a non-muscular contractile system, constructed by inner ovarian epithelium cells, and they have shown that smooth-muscle cells are present in the theca of interfollicular regions, but never in the follicle itself.…”
Section: Biological Resultsmentioning
confidence: 93%
“…Direct observation of electronmicrographs of follicles does not reveal any smooth muscle fibres. Anderson & Yatvin (1970) pointed out that the absence of smooth muscle in a variety of amphibians raised the question of the source of the squeezing phenomenon accompany¬ ing ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…A pool of large uniformly sized ovarian follicles from each animal were manually removed from ovaries under magnification (Wild MJ-dissecting microscope) with watchmakers forceps. By varying the technique of manual dissection, oocytes were either stripped of (1) surface epithelium, or (2) both the surface epithelium and theca layer. The normal defolliculation process typically removes both of these outer layers leaving the oocyte encased by a single layer of follicle cells which remain attached to the outer surface of the vitelline membrane [lo, 24, 261.…”
Section: General Proceduresmentioning
confidence: 99%